Legal Study On Handling Cases Of Sextortion Involving Minors As Perpetrators And Victims In Indonesia - Wibowo, Fian Agung; Permana, Indra Surya (Fakultas Hukum Dehasen, 2025)
Sextortion involving children as both perpetrators and victims is a serious issue that requires a comprehensive legal approach in Indonesia. This study aims to analyze the effectiveness of existing regulations and challenges in the legal protection of children in sextortion cases. The research uses a normative juridical method by examining relevant laws such as the Child Criminal Justice System Law (UU SPPA), Pornography Law, Electronic Information and Transactions Law (UU ITE), and Sexual Violence Law (UU TPKS). The results indicate that although various regulations exist, challenges remain in ensuring consistent law enforcement, special protection for child victims, and adequate trauma management. In conclusion, improvements in law enforcement, inter-agency coordination, and increased public awareness are needed to protect children from digital-based crimes